Redesain Tata Letak Taman Bermain Outdoor Santri Raudhatul Atfal dengan Metode Design Thinking yang Ergonomis - Wahyudin Wahyudin; Dene Herwanto; Billy Nugraha (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
Playground equipment in kindergarten is one of the facilities and facilities that need attention. Given the large function and benefits of these tools in children's learning or playing activities. This study aims to redesign the layout of several playing tools, including: slide, globe climbing, and ergonomic ring bridges according to anthropometric data of R.A Nurul Iman Kindergarten students. This data is used as a parameter in making the latest ergonomically proposed design. The research steps carried out in designing a play tool use an ergonomic design thinking method. The research results were obtained from the redesign of the playing tool. Redesign of the game slide, globe climbing, and ring bridge accompanied by sizes that match the anthropometric data of the students obtained. There are 9 dimensions of the body that are taken in this study with the applied method, divided into 3 stages: inspiration, ideanation and implementation.